Comfort from Hearing Protectors - Behar, Alberto; Segu, Roopa; Russo, Frank (Canadian Acoustics, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Comfort in an important property of hearing protectors, perhaps as important as the sound attenuation. If a protector is deemed to be uncomfortable, it will not be worn or it is modified in some manner by the user, often to the detriment of the attenuation. Although doubtless important, this characteristic is not studied as often as it should. A search conducted on the database Web of Science, shows that between the years 1970 and 2014, 208 papers were published dealing with attenuation in hearing protectors, while there were only 22 papers related to comfort. One reason for the scarcity of research on comfort could be the lack of a consistent definition, due to its inherently subjective nature. Another is the dependency of comfort on factors other than the protector itself, such as temperature and humidity of the workplace and the need for intelligibility. Finally, there are the anatomical differences among wearers that cause differences of comfort. This paper analyzes comfort studies done in the last 25 years, with the intent of developing a procedure to rank hearing protectors on the basis of comfort under specified conditions. An additional aim is to assess the tradeoff between comfort and attenuation across different types of protectors, since some situations may allow for a lower attenuation in favor of a increased comfort. In addition, we intend to develop a mathematical model for predicting comfort for different types of protectors. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->